On the Problem of Best Rational Approximation with Interpolating Constraints (II) (Journal of Computational Mathematics, 1990)
This paper is a continuation of [2]. In this part of the conjoint paper, we establish some results about uniqueness /non-uniqueness, the properties for the set of best approximants, strong uniqueness and continuity of the best approximation operator.